The Rhetorical Structure of Students’ Presentation in Speaking Class - Novitasari, Heryanti; Syafryadin, Syafryadin; Sofyan, Dedi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
This study aims to find the rhetorical structure of Move and Step which are often found in the Speaking for Presentation class. Additionally, this research looks into the typical pattern of studentsâ€™ presentations in the Speaking for Presentation class. This study used a mixed-method research strategy that incorporates qualitative and quantitative data. The object of the research is 30 video presentations of 4th-semester English education students from the Speaking for Presentation class at Bengkulu University. From this study, it was found that the rhetorical structures of the Moves and steps that are most often found in students' presentations in the Speaking for Presentation class are Greeting the audience, Introduction of oneself/other speakers, Announcing the topic of oral presentation, Hortatory/narration, Summarizing the points/conclusion, and Thanking/Thank you. Then, the second of the Moves and the steps that are most often found in students' presentations in the Speaking for Presentation class are Leading the audience into the content and Suggestion. Furthermore, the typical patterns found in student presentations are Obligatory and Conventional.Â